The relationship between the ratio of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol (NHHR) and both MASLD and advanced liver fibrosis: evidence from NHANES 2017–2020 - Li, Juyi; Kou, Chunjia; Chai, Yuwei; Li, Yuchen; Liu, Xue; Zhang, Li; Zhang, Haiqing (Frontiers in Nutrition, 2025)
BackgroundThe non-HDL-C to HDL-C ratio (NHHR) is a dependable lipid marker linked to atherosclerotic traits. This study examines the potential relationship between NHHR and both metabolic dysfunction-associated steatotic liver disease (MASLD) and advanced liver fibrosis.MethodsThis study investigated the relationship between NHHR levels and both MASLD and advanced liver fibrosis using data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) in the United States. First, we conducted a baseline characteristics analysis of the population based on NHHR quartiles. Second, we employed multivariable weighted linear regression models to examine the associations between NHHR and MASLD, as well as advanced liver fibrosis. Third, we utilized restricted cubic splines (RCS) to assess potential non-linear relationships. Fourth, we performed subgroup analyses. Finally, ROC curve analysis was conducted to evaluate the effectiveness of NHHR.ResultsIn the main analysis, this study included a total of 9,864 participants. Following multivariable logistic regression and comprehensive adjustments, elevated NHHR levels in the Q3 and Q4 groups were significantly linked to MASLD, with odds ratios of 1.59 (95% CI: 1.20–2.11) and 1.83 (95% CI: 1.40–2.39), respectively (P for trend < 0.0001). Elevated NHHR levels in the Q2 and Q3 groups remained significantly linked to a decreased risk of advanced liver fibrosis, with odds ratios of 0.61 (95% CI 0.40–0.94, P = 0.03) and 0.64 (95% CI 0.47–0.89, P = 0.01), respectively. RCS analysis revealed a U-shaped nonlinear association between NHHR and both MASLD (P = 0.000; P for nonlinear = 0.029) and advanced liver fibrosis (P = 0.0001; P for nonlinear = 0.000). In the subgroup analysis, we found that this relationship was significant only in certain subgroups. The ROC curve analysis revealed that NHHR exhibited the best predictive performance for diagnosing MASLD based on the fatty liver index (FLI). The optimal cutoff point for NHHR in predicting MASLD using FLI was determined to be 2.476, with sensitivity and specificity values of 0.589 and 0.698, respectively.ConclusionNHHR may serve as a predictive marker for MASLD and advanced liver fibrosis, highlighting its potential significance in risk assessment and prevention strategies.